Integration of Waste-to-Energy in Physics Learning: An Andragogical Approach for Sustainable Education - Hermansyah, Hermansyah; Yustiana, Yusi Riksa; Kaniawati, Ida; Liliawati, Winny (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This study explores the integration of Waste-to-Energy (WTE) concept with andragogical approach to enhance physics learning in supporting sustainable education. This descriptive qualitative research involved 14 students and 1 lecturer from a private university in Sumbawa, NTB, through questionnaires and semi-structured interviews. The results showed that the introduction of WTE was relevant in deepening students' understanding of renewable energy and thermodynamics, while increasing their engagement through experiential learning. The andragogical approach proved effective, despite the limited resources and complexity of the material. This study offers practical implications for physics teaching, namely the importance of integrating sustainability and renewable energy themes in the curriculum to prepare students to face global challenges in the fields of energy and the environment.